“Complicaciones crónicas asociadas a diabetes mellitus tipo 2 en pacientes geriátricos. Riobamba, 2019 - 2020”. - Sigcho Ajila, Jimmy Andrés (2020)
Introduction: Type 2 Diabetes Mellitus is considered a frequent chronic pathology, which is on the rise in recent decades worldwide, being a disease causing high morbidity and mortality in our country. Objective: Determine the factors associated with the increase of chronic complications of DM2 of geriatric patients of the Hospital General IESS Riobamba. Method: The research descriptive, cross-sectional, observational and retrospective since information was taken at a time of January, 2019 - February, 2020 to the population of 120 geriatric adults over 60 years old in the Hospital General IESS Riobamba. Results and conclusions: 56% (64) were women and 46.7% (56) men, with the mean age of 70.8 years, 40% (48) with primary education, in terms of geographic location 67.8% (81) live in the urban area and 32.5% (39) rural, in the study population, arterial hypertension stands out as comorbid with 57.5% (69) and as Nephropathy as a chronic complication in 26.7% (32) of the subjects. The treatment was insulin therapy in 46.7% (56) of the cases and only 0.8% (1) used non-pharmacological therapy such as diet and exercise. Age older than 80 years was a risk factor for developing heart disease, and high blood pressure for developing complications such as retinopathy, heart disease, and kidney disease.